Effect of Cow Manure Bokashi Dosage on Growth and Production of Peanuts (Arachis hypogeae L.) - Anti, Wa Ode; Rogalendo, Abdul Jaman; Rahim, Abdul; Roswuro, Roswuro; Samiati, Samiati (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2023)
This research aims to determine the effect of cow dung bokashi dosage on the growth and production of peanut plants in carried out this research in Wanseriwu Village, Central Tiworo District, West Muna Regency, Southeast Sulawesi Province. The materials used are cow manure, EM4, granulated sugar, water, urea fertilizer, SP 36, KCl, and mouse deer variety peanut seeds. The tools used were hoes, machetes, wood, meters, raffia rope, buckets, scales, small spoons, label boards, sprayers, thermometers, small containers/bowls for seeds, and writing utensils. This research organized based on a Randomized Block Design (RAK) with five treatments consisting of B0: without cow dung bokashi, B1: cow dung bokashi with a dose of 3 kg plot-1 or 10 t ha, B2: cow dung bokashi with a quantity of 6 kg plot-1 or 20 t ha-1, B3: cow dung bokashi with an amount of 9 kg plot-1 or 30 t ha-1, B4: cow dung bokashi with a dose of 12 kg plot-1 or 40 t ha-1. The parameters observed were plant height (cm) carried out at 2, 4, 6, and 8 weeks after planting, number of stem branches) carried out at 2, 4, 6, and 8 weeks after planting, number of pods formed, number of filled pods, weight planting seeds (g), and weight of 100 dry seeds (g). Giving cow dung bokashi at different doses significantly affected plant height, number of branches, number of pods formed, number of filled pods, weight of seeds per plant, and weight of 100 dry seeds. Bokashi cow dung at a dose of 40 t ha-1 provides the best growth and production of peanuts, with an average dry seed weight per plant reaching 36.71 g plant-1 or 3.06 t ha-1.